2013
DOI: 10.1590/s1983-40632013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit in cotton plant originated from seeds treated with growth regulator

Abstract: Mepiquat chloride (MC) is widely used for controlling cotton plant growth. Shoot growth modifications may affect root growth and, consequently, interfere with the cotton sensitivity to water deficit. This study aimed at evaluating the water deficit effects, in initial phenological stages of cotton plants from seeds treated with MC doses, on shoot and root growth. Two experiments were carried out in a greenhouse, in Santa Helena de Goiás, Goiás State, Brazil, in a randomized blocks design, in a 4x4 factorial sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Pace et al (1999) measured the root and shoot parameters of cotton grown under drought and observed reduction in growth, development, and distribution of stressed cotton plants roots as compared to control treatments. Similarly, reduction in root dry matter due to water deficit in cotton plant has been observed by Ferreira et al (2013). Pace et al (1999).…”
Section: Effect Of Drought Stress On Various Morphologicalsupporting
confidence: 55%
“…Pace et al (1999) measured the root and shoot parameters of cotton grown under drought and observed reduction in growth, development, and distribution of stressed cotton plants roots as compared to control treatments. Similarly, reduction in root dry matter due to water deficit in cotton plant has been observed by Ferreira et al (2013). Pace et al (1999).…”
Section: Effect Of Drought Stress On Various Morphologicalsupporting
confidence: 55%
“…On average, the reductions were 20.2%, 32.5%, 36.9% and 33.6%, in water regimes of 80%, 60%, 40% e 20% of evapotranspiration replacement, respectively. Other reports also observed that water stress reduced the overall plant stature of cotton (Baldo et al, 2009;Ferreira et al, 2013). According to the first authors, this occurred concomitantly with a 35% reduction in leaf-area index, prompting an 8% reduction in solar radiation interception.…”
Section: Resultsmentioning
confidence: 88%
“…Plant height decreased under skip irrigation, which might be due to varietal characteristics and less water availability. Ferreira et al (2013) found reduction in root and shoot length of matured cotton crops under water deficit conditions. Shoot length and dry matter contents of stressed cotton plants decreased which might be due to less growth in water scarcity conditions.…”
Section: Discussionmentioning
confidence: 91%